GCR flux decline during the last three centuries: extraterrestrial and terrestrial evidences - CINI, Giuliana; Cane D.; TARICCO, Carla; Bhandari N. (UAP-Universal Academy Press, 2003)
We have deduced the Galactic Cosmic Ray (GCR) annual mean spectra for the last 300 years (Bonino et al., 2001), using the open solar magnetic flux proposed by Solanki et al. (2000). From the GCR proton flux we have calculated the 44 T i (T1/2 =59.2 y) activity in small stony meteorites and we have compared it with our measurements of the cosmogenic 44 T i in different H chondrites fell in the period 1810-1997 (Bonino et al., 2003). The results are in close agreement both in phase and amplitude. The same primary flux has been used for calculating the production rate of 10 be in the atmosphere of the Earth (using the model by Masarik and Beer, 1999), which is found to be in good agreement with its concentration profile measured in Dye3 ice core from Greenland. The results are all consistent with a decreasing flux of GCR over the past three centuries.